A long-term study of size variation in Northern Goshawk Accipiter gentilis across Scandinavia, with a focus on Norway - Walker, Samuel; Lislevand, Terje; Meijer, Hanneke (Zenodo, 2023)
Changing climate and growing human impacts are resulting in globally rising temperatures and the widespread loss of habitats. How species will adapt to these changes is not well understood. The Northern Goshawk ( Accipiter gentilis ) can be found across the Holarctic but is coming under more intense pressure in many places. Studies of recent populations in Finland and Denmark have shown a marked decline in body size of Northern Goshawks over the past century. Here we investigate long-term changes to Norwegian populations of Northern Goshawk by including material from the Middle Ages. We measured 240 skeletons of modern Northern Goshawks from Norway, Sweden, Denmark and Finland, and 89 Medieval Goshawk bones. Our results show that Norwegian and Swedish female Goshawks have decreased in size over the past century, whilst males showed little decline. Medieval female Goshawks were larger than contemporary females. A decline in forest habitats and a concomitant shift towards smaller prey likely drove a shift to smaller body size in Northern Goshawks. Our study shows that significant body size changes in birds can occur over relatively short time spans in response to environmental factors, and that these effects can sometimes differ between sexes. Funding provided by: University Museum of Bergen* Crossref Funder Registry ID: Award Number: Funding provided by: European Commission Crossref Funder Registry ID: https://ror.org/00k4n6c32 Award Number: DK-TAF-2419 Funding provided by: European Commission Crossref Funder Registry ID: https://ror.org/00k4n6c32 Award Number: FI-TAF-2548 Modern comparative material To analyse changes in both modern and past populations of A. gentilis , metric data of the nominate Accipiter gentilis gentilis were collected from across the Nordic countries (Norway, Sweden, Denmark and Finland). The Northern Goshawk is a sedentary species, generally choosing to breed and winter in the same area. There are some exceptions to this in North America, Fennoscandia and Russia (Squires et al., 2020). ...